ENHANCING MOTHERS’ PARENTING SKILLS THROUGH EMOTION REGULATION EDUCATION IN JATIREJO VILLAGE, NGANJUK - Nicky Dwi Kurnia; Febi Warta Nur Ani; Binti Kholifah (Jurnal Layanan Masyarakat (Journal of Public Services), 2026)
Parenting in rural communities still faces various challenges, particularly related to parents’ ability to regulate emotions when dealing with children’s behavior. Limited access to parenting information and socio-economic pressures often affect the quality of parent–child interactions. This community service program aimed to improve mothers’ understanding and skills in applying emotion regulation–based parenting in Jatirejo Village, Rejoso District, Nganjuk Regency. The program involved 40 mothers with children under the age of 10 and was conducted on August 20–22, 2025, at the Jatirejo Village Hall with the support of lecturers and students participating in the Community Service Program (KKN) from Institut Teknologi Mojosari. The program employed a mixed approach through participatory education, group discussions, and parenting simulations. Program evaluation was conducted using participatory observation, reflective interviews, and descriptive measurements based on rating scales. The novelty of this program lies in the integration of emotion regulation education with a reflective approach based on mothers’ real parenting experiences within the village community, enabling participants not only to receive knowledge but also to reflect on their daily parenting practices. The results showed an improvement in mothers’ emotion regulation skills, indicated by an increase in observation scores from 2.15 to 3.12 and reflective interview scores from 2.05 to 3.20. These changes were reflected in mothers becoming calmer, more patient, and more responsive in dealing with children’s behavior. In addition to improving mother–child interactions, the program also strengthened social support among mothers within the community. Therefore, emotion regulation–based parenting education is considered an effective and contextual approach to improving parenting quality in rural communities. Future programs are recommended to be implemented sustainably by integrating similar initiatives into family empowerment activities at the village level.